Management and assessment of innovation environments - Marcelo Amaral (Triple Helix, 2015)
This article describes and assesses the management of innovation environments, such as business incubators and science, technology, and innovation parks, resulting from university-industry-government (UIG) linkages. It also reviews recent literature in which three different methods are presented and combined: Da Poian's 11 factors, Estrategigram, and the method Centro de Referência para Apoio a Novos Empreendimentos (CERNE)-'Reference Center to Support New Ventures.' The resulting model, named 'Amaral's Model for Innovation Environment Management' (AMIEM), was applied to five cases in Brazil. The empirical results are useful for analyzing such environments independently and for comparing them with a scoring system, based on the maturity level of each environment, which can be a way to evaluate the internal development and UIG linkages. These actors have developed in Brazil in the past 30~years in diverse innovation environments. However, several weaknesses in UIG linkages exist, and actions are necessary to promote enhancement, develop hybrid contexts and consensus spaces, and multiply experiences, creating more innovation and prosperity in the Brazilian economy.
Keywords: O31; O32; L26; M13; 330; Triple Helix; Assessment; Business incubators; Science; technology and innovation parks; University-industry-government